Pengaruh Metode Fermentasi Dan Pengeringan Terhadap Mutu Biji Kopi Arabika (Coffea arabica L.) - I Wayan Swiranata; I Gede Pasek Mangku; I Nyoman Rudianta (GEMA AGRO, 2020)
Kintamani Arabica coffee has good quality and has a distinctive characteristic of having an orange flavor. The quality of the coffee beans is influenced by several processing method. The fermentation and drying processes are the main keys in producing quality Arabica coffee beans. This study aims to obtain arabica coffee beans with the appropriate quality standard of SNI. This research was conducted at the Processing Laboratory, Faculty of Agriculture, Warmadewa University. This study was designed with a Completely Randomized Design (CRD) consisting of 2 (two) factors, namely: Factor I, the fermentation method consisting of 3 levels, namely: No fermentation, temperature fermentation (30± 1oC), 48 hours long, temperature fermentation (50± 1oC) 24 hour duration. Second factor, the drying method consists of 3 types, namely: sun drying, oven temperature drying (50± 1oC), oven temperature drying (60± 1oC). The variables observed for Arabica coffee beans included objective observations: moisture content, weight loss, caffeine content, color intensity. Objectively quality Arabica coffee beans obtained from the treatment of the temperature fermentation method (30± 1oC) for 48 hours with drying at oven temperature (60± 1oC) for 8 days. With the characteristics of water content (5,435%), weight loss (79,183%), caffeine content (0,918%), L * color (44,640), color a * (3,275), color b * (24,815) which are in accordance with SNI No quality requirements. . 01-29 03-2017.